In vivo prostacyclin biosynthesis and effects of different aspirin regimens in patients with essential thrombocythaemia - Cavalca, Viviana; Rocca, Bianca; Squellerio, Isabella; Dragani, Alfredo; Veglia, Fabrizio; Pagliaccia, Francesca; Porro, Benedetta; Barbieri, Silvia Stella; Tremoli, Elena; Patrono, Carlo (Thrombosis and Haemostasis, 2014)
Essential thrombocythaemia (ET) is characterised by enhanced platelet generation and thrombosis. Once daily (od) aspirin incompletely inhibits platelet thromboxane (TX)A2 production in ET. A twice daily (bid) dosing is necessary to fully inhibit TXA2. Whether this dosing regimen affects in vivo prostacyclin (PGI2) biosynthesis is unknown. PGI2 biosynthesis was characterised in 50 ET patients on enteric-coated (EC) aspirin 100 mg od, by measuring its urinary metabolite, 2,3-dinor-6-keto-PGF1α (PGI-M). Moreover, in a crossover study 22 patients poorly responsive to standard aspirin based on serum TXB2 levels (>4 ng/ml) were randomised to different seven-day aspirin regimens: EC aspirin 100 mg od, 100 mg bid, 200 mg od, or plain as-pirin 100 mg od. PGI-M measured 24 hours after the last aspirin intake (EC, 100 mg od) was similar in patients and healthy subjects both on (n=10) and off (n=30) aspirin. PGI-M was unrelated to in vivo TXA2 biosynthesis, and not affected by EC aspirin 100 mg bid or 200 mg od as compared to EC 100 mg od. PGI2 biosynthesis in aspirin-treated ET patients appears unrelated to TXA2 biosynthesis, and not affected by an improved aspirin regimen, demonstrating its vascular safety for future trials.
Keywords: Aspirin; prostacyclin; essential thrombocythaemia; platelets; thromboxane